Improving livestock research and technology transfer in developing countries - Ehui, Simeon K.; Shapiro, Barry I. (International Livestock Research Institute, 2004)
This paper addresses issues related to the roles and actions that the different partners in livestock research and Development can take to increase co-operation, ensure more effective technology transfer and increase impact. The focus is on Africa, because this region, while not being unique in facing the problems of the developing world, provides the greatest challenges to the global agricultural Development community. After reviewing the current state of agricultural research efforts, and the policy environment for livestock research, including the effects of sectoral and macro policies, the special need for making the case to support livestock research is highlighted. Then the rationalisation of the roles for the different partners in livestock research is proposed. Next, new modalities for linking research and technology transfer are discussed, as well as where the needed resources in the future could come from. Finally, the conclusions and the recommendation for a framework for action to promote livestock Development are presented. Topics of discussion include the current state of research efforts; the livestock research policy environment; sectoral and macro policy effects on livestock research impact; making the case for livestock research; research strategies to promote livestock Development goals; linking research and technology transfer; and where the needed resources come from.